3D vibrations reconstruction with only one camera. (1st January 2022) - Renaud, Franck; Lo Feudo, Stefania; Dion, Jean-Luc; Goeller, Adrien
Abstract: In this paper, we propose a new method to measure the vibrations of a 3D mechanical structure. It requires only a video sequence taken by a single camera and a Finite Element model of the structure. First, the intrinsic and extrinsic parameters of the camera are identified. Then, a collection of numerical deflection shapes and normal modes are projected in the image frame of the camera. This is done thanks to a linearization of the perspective projection model. Comparing the motion of targets seen by the camera and the motion of Finite Element model at the same location gives the time evolution of modes amplitude. Finally the motion of the model is reconstructed in 2D in the image frame and in 3D in the world frame. By following this procedure, vibration amplitude can be magnified applying a scale factor on a modal basis covering a large frequency bandwidth. Highlights: New method for 3D vibrations reconstruction with only one camera. 3D vibrations are identified by projection on the image frame of FE eigenmodes. Projection is done thanks to a linearization of the perspective projection. Vibration can be magnified thanks to the scale factor of the eigenmodes. Extension to several cameras is possible without any overlapping field of view.